Limitless Borderless Forgetfulness? Limiting the Geographical Reach of the ‘Right to be Forgotten’ - Dan Jerker B Svantesson (Oslo Law Review, 2015)
Abstract In Google Spain, the Court of Justice of the European Union ruled that, in certain circumstances, the operator of a search engine is obliged to remove search results from the list of results displayed following a search made on the basis of a person’s name. In respect of implementation of this ‘right to be forgotten’ — or more accurately ‘right to delisting’ — one of the most important issues relates to the geographical scope of the delisting; that is, once it is decided that certain search results should be delisted, what is the appropriate geographical scope of the delisting? Google is currently only delisting in relation to EU domains such as .es, .nl and .de. However, in sharp contrast, the EU’s Article 29 Working Party on data protection wants global blocking so as to ensure that EU law is not ‘circumvented’. This article canvasses the contours of this issue and attempts to advance its resolution by proposing a Model Code for Determining the Geographical Scope of Delisting Under the Right To Delisting. While the Model is presented in the EU context, it can easily be transplanted into other jurisdictions as well.